FAKTOR YANG BERHUBUNGAN DENGAN PENURUNAN PENGGUNAAN KONTRASEPSI DI MASA PANDEMI COVID-19 DI KLINIK PRATAMA MUTIA, KABUPATEN DELI SERDANG TAHUN 2022 - Mutia, Lany; Santoso, Ileru; Tarigan, Frida Lina; Sabriyanto (Akupun Tour Publisher, 2024)
Background: Indonesia is a developing country with a population that ranks fourth highest in the world in terms of population growth rate and population after China, India and the United States. Purpose: This study aims to analyze the factors with a decrease in contraceptive use in PUS during the Covid-19 pandemic at Pratama Mutia Clinic, Deli Serdang in 2022. Method: This research design uses an analytic method of this research also through a quantitative approach in a cross sectional manner. The population in this study were 126 couples of childbearing age who were actively practicing family planning according to 2021 data taken in December 2021 at the Pratama Mutia Clinic. The accidental sampling technique is a sampling technique based on chance, namely PUS who utilize family planning facilities at the Pratama Mutia Clinic during the study. The sample selected for the questionnaire test was not selected again as a respondent at the time of the study so as not to be biased. Data collection techniques using questionnaire sheets and respondent observation sheets. Data analysis techniques using the Che-Square Test. Results : Based on the bivariate results, it shows that the p-value = 0.012 (Knowledge), p-value = 0.008 (Parity), p-value = 0.045 (Economy), p-value = 0.021 (Husband Support), p-value = 0.038 (Health Worker Support), through the multivariate test Based on the above equation, it is known that if the respondent has poor knowledge and does not get husband support and support from health workers, the probability of respondents experiencing a decrease in contraceptive use during the covid-19 pandemic is 33.8%. Disscusion and Conclusion: Based on the results of the study, the following conclusions can be drawn that knowledge, husband support and health worker support have the greatest influence on reducing the use of contraceptive methods. Suggestion: To increase knowledge about contraceptive methods will be used by family planning acceptors, especially in the field of family planning, namely the Decrease in Contraceptive Use and Factors Related to the Survey in PUS during the Covid-19 Pandemic at Pratama Mutia Clinic, Deli Serdang.